REBOA at Role 2 Afloat: resuscitative endovascular balloon occlusion of the aorta as a bridge to damage control surgery in the military maritime setting. Issue 2 (20th December 2017) - Rees, Paul; Waller, B; Buckley, A M; Doran, C; Bland, S; Scott, T; Matthews, J
Abstract : Role 2 Afloat provides a damage control resuscitation and surgery facility in support of maritime, littoral and aviation operations. Resuscitative endovascular balloon occlusion of the aorta (REBOA) offers a rapid, effective solution to exsanguinating haemorrhage from pelvic and non-compressible torso haemorrhage. It should be considered when the patient presents in a peri-arrest state, if surgery is likely to be delayed, or where the single operating table is occupied by another case. This paper will outline the data in support of endovascular haemorrhage control, describe the technique and explore how REBOA could be delivered using equipment currently available in the Royal Navy Role 2 Afloat equipment module. Also discussed are potential future directions in endovascular resuscitation.